Pharmacokinetic and pharmacodynamic principles: unique considerations for optimal design of neonatal clinical trials - Yeung, Cindy Hoi Ting; Verstegen, Ruud H. J.; Greenberg, Rachel; Lewis, Tamorah Rae (Frontiers in Pediatrics, 2024)
Core clinical pharmacology principles must be considered when designing and executing neonatal clinical trials. In this review, the authors discuss important aspects of drug dose selection, pharmacokinetics, pharmacogenetics and pharmacodynamics that stakeholders may consider when undertaking a neonatal or infant clinical trial.